The Effect of Esg Score on Firm Performance With the Moderating Role of Board Independence: (A Study on Financial Sector Companies) - Khairu Athaya; Sari Sembiring (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study analyzes the transition of the Indonesian financial sector toward a sustainable financial ecosystem by examining the impact of Environmental, Social, and Governance (ESG) performance on firm profitability. Despite the regulatory push for sustainable finance, market responses to non-financial disclosures remain mixed, raising questions about whether sustainability practices genuinely enhance asset efficiency or merely impose administrative burdens. This study aims to investigate the effect of ESG Scores on Firm Performance and evaluate whether Board Independence acts as an internal governance mechanism to moderate this relationship. Utilizing a quantitative approach, a purposive sample of 30 financial companies listed on the Indonesia Stock Exchange was observed from 2021 to 2023, yielding 90 firm-year observations analyzed via panel data regression with mean-centered Moderated Regression Analysis (MRA). The empirical results reveal that ESG Scores have an insignificant negative impact on Return on Assets (ROA). Furthermore, Board Independence fails to moderate the relationship. These findings conclude that ESG integration in Indonesia is currently compliance-driven rather than substantive, where the short-term structural costs of sustainability disclosure still outweigh its immediate accounting returns.